2021
DOI: 10.3390/molecules26082299
|View full text |Cite
|
Sign up to set email alerts
|

Deconstruction of Lignin: From Enzymes to Microorganisms

Abstract: Lignocellulosic residues are low-cost abundant feedstocks that can be used for industrial applications. However, their recalcitrance currently makes lignocellulose use limited. In natural environments, microbial communities can completely deconstruct lignocellulose by synergistic action of a set of enzymes and proteins. Microbial degradation of lignin by fungi, important lignin degraders in nature, has been intensively studied. More recently, bacteria have also been described as able to break down lignin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 119 publications
1
29
0
Order By: Relevance
“…Lignocellulose is mainly composed of lignin, cellulose, and hemicellulose, forming a highly complex and varying polymeric structure that is highly recalcitrant to degradation and thus requires a consortium of carbohydrate-active enzymes (CAZymes) that act in synergism to provide its complete decomposition [ 11 ]. Lignin degradation is an enzymatic oxidation catalyzed by two main groups of enzymes, namely, lignin-modifying enzymes (LMEs) and lignin-degrading auxiliary (LDA) enzymes [ 12 ]. In contrast to lignin degradation, enzymatic degradation of cellulose and hemicellulose is mainly mediated by a process of hydrolysis through the action of glycoside hydrolases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignocellulose is mainly composed of lignin, cellulose, and hemicellulose, forming a highly complex and varying polymeric structure that is highly recalcitrant to degradation and thus requires a consortium of carbohydrate-active enzymes (CAZymes) that act in synergism to provide its complete decomposition [ 11 ]. Lignin degradation is an enzymatic oxidation catalyzed by two main groups of enzymes, namely, lignin-modifying enzymes (LMEs) and lignin-degrading auxiliary (LDA) enzymes [ 12 ]. In contrast to lignin degradation, enzymatic degradation of cellulose and hemicellulose is mainly mediated by a process of hydrolysis through the action of glycoside hydrolases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have indicated that the efficiency of lignocellulose degradation can be remarkably improved by the cooperative action of lytic polysaccharide monooxygenases (LPMOs), which are able to directly oxidize and depolymerize insoluble crystalline substrate surfaces or soluble hemicellulosic substrates such as xyloglucan, xylan, and β-glucans [ 14 16 ]. In natural ecosystems, the degradation of lignocellulosic biomass is mainly dependent on a repertoire of enzymes produced by bacteria and fungi [ 11 , 12 ]. However, more efficient degradation can be achieved by host eukaryotes working together with their gut microorganisms (often referred to as a “holobiont”) [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods produce a wide range of products of importance such as pyro char, bio-oil, ethylene benzene and others [ 6 ], they have several drawbacks such as high-energy demands, complicated process control and complex product formation due to the general inertness of lignin [ 6 , 32 ]. Moreover, the poorly established methods may lead to other modifications to lignin resulting in increased recalcitrance and subsequent difficulty in the separation of the desired products from the repolymerised lignin [ 21 , 33 , 34 , 35 ]. In a world of a fast-growing population, dwindling resources and climate change, such unsustainable methods of lignin depolymerisation are being challenged by a much more attractive biological valorisation approach.…”
Section: Lignin Waste Stream Backgroundmentioning
confidence: 99%
“…Common single fungi cannot achieve complete degradation of lignocellulose ( Karuppiah et al, 2021 ). Research shows that different microorganisms in the microbial community operate synergistically through the secretion of a variety of biocatalysts, in order to achieve comprehensive enzyme production to degrade lignocellulose ( Silva et al, 2021 ). Therefore, we can use the method of artificial screening and mixing, fungi producing different enzymes in the same medium for co-culture to improve the degradation rate of lignocellulose.…”
Section: Introductionmentioning
confidence: 99%